45, X/47, XY, +13 MOSAICISM IN A 15-YEAR-OLD GIRL - Saad, Ghada; Majdoub, Marwa; Slama, Nassim Ben Hadj; Dimassi, Sarra; Kacem, Maha; ACH, Koussay (Journal of the ASEAN Federation of Endocrine Societies, 2022)
BACKGROUND Approximately 45% of postnatal Turner syndrome patients have a pure 45,X cell line. Other karyotypes that may be mosaic with 45,X most commonly include:46,XX,; 47,XXX; or 46,XY;The presence of a 46,XY cell line may occur in 5–10%. Only a few instances of mosaicism with X-monosomic and trisomic cell lines of 21, 18, 13 were described. CASE We report the case of a 15-year-old female consulting for pubertal delay. Physical examination revealed the following signs of Turner syndrome: short stature, cubitus valgus lack of secondary sexual signs, brachymetacarpia and cutaneous nevi while no features of trisomy 13 were present. She showed female type of external genitalia. LH and FSH were elevated (100 and 21.5 mUI/l), serum estradiol: <10 pg/ml, serum testosterone: 0.1 ng/ml. Chromosomal analysis revealed a complicated karyotype: 45,X/47,XY,+ 13 mosaicism. The culture of skin fibroblasts, however, showed only 45,X cells. The coelioscopy showed a hypoplastic uterus and the histological examination of the castrated gonads showed ovarian agenesis. Our patient had no complication of Turner syndrome nor of 13 trisomy except for the agenesis of her corpus callosum. CONCLUSION Despite her pathological karyotype, this patient had a Turner syndrome phenotype with no complication, no evidence of any androgen effect and no detected malformations. The phenotype in a 45,X/46,XY mosaic patient likely depends on the distribution of mosaicism percentage in different tissues. We suggest that additional cells should be analyzed and more molecular genetic studies should be conducted.